2018
DOI: 10.3389/fpsyg.2018.02063
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Different Reference Frames: How Stimulus Setup and Task Setup Shape Egocentric and Allocentric Simon Effects

Abstract: Different reference frames are used in daily life in order to structure the environment. The two-choice Simon task setting has been used to investigate how task-irrelevant spatial information influences human cognitive control. In recent studies, a Go/NoGo Simon task setting was used in order to divide the Simon task between a pair of participants. Yet, not only a human co-actor, but also even an attention-grabbing object can provide sufficient reference in order to reintroduce a Simon effect (SE) indicating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
(78 reference statements)
2
3
0
Order By: Relevance
“…The interaction of Display Size and Ball Position Compatibility, indicating differences in the local Simon effect, was non-significant, F(1, 203) = 3.63, p = .058, ƞ p 2 = .018. These results are comparable to those observed in other work of our group with a two-choice Simon task and even comparable to our results found in a Go/No-Go version of this task (Baess et al, 2018).…”
Section: Reaction Timessupporting
confidence: 93%
See 3 more Smart Citations
“…The interaction of Display Size and Ball Position Compatibility, indicating differences in the local Simon effect, was non-significant, F(1, 203) = 3.63, p = .058, ƞ p 2 = .018. These results are comparable to those observed in other work of our group with a two-choice Simon task and even comparable to our results found in a Go/No-Go version of this task (Baess et al, 2018).…”
Section: Reaction Timessupporting
confidence: 93%
“…Additionally, we used a paradigm with manikins holding colored balls to measure global and local Simon effects. This paradigm has been used in different studies with German samples Baess et al, 2018), which found results identical to the ones of German participants in the present study. To ensure the cultural differences in local and global Simon effects observed in the present study are reliable, other versions of the Simon paradigm, for example one with horizontally aligned reference boxes (for review, , or even other paradigms investigating response selection in spatial tasks, should be employed.…”
Section: Limitationssupporting
confidence: 75%
See 2 more Smart Citations
“…The idea of using SRC effects to examine other cognitive phenomena is not new (e.g., Hommel, 2011) and has already been used in the context of perspective taking to quantify the influence of a conflicting reference frame, either of a person (Freundlieb, Kovács, & Sebanz, 2016), an avatar (Böffel & Müsseler, 2018, 2019a, b, 2020aMüsseler et al, 2019) or even simple manikins (Baess, Weber, & Bermeitinger, 2018). Because SRC has been shown to be dependent on context and intention (Hommel, 1993;Müsseler, Aschersleben, Arning, & Proctor, 2012), it seems to emerge based on the mental representation of an event, rather than on its mere physical reality.…”
Section: Stimulus-response Compatibility As An Indicator Of Cognitivementioning
confidence: 99%